Evaluation of Multivariate Integrals via Fluctuationlessness Theorem and Taylor's Remainder - (:unkn) unknown (AMER INST PHYSICS, 2009)
A recently developed Fluctuationlessness Method is used in approximating the multiple remainder terms of the integral of the multivariate Taylor expansion. This provides us with a new numerical integration method for multivariate functions.
Keywords: Multivariate Approximation; Numerical Integration; Multivariate Taylor's Theorem; Fluctuationlessness Theorem; EXPANSION